Czech Republic : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report, 2004)
This paper presents an update to the Report on the Observance of Standards and Codes-Fiscal Transparency Module for the Czech Republic. The paper reports on key developments in fiscal transparency since the last update in August 2003. It discusses that since the last update, the fiscal coverage of the general government has been broadened by including the financial subsidiaries of the Czech Consolidation Agency, including Ceska inkasni, and the Viticulture Fund. However, the impact on the general government's fiscal balance and debt was fairly small.